Unsteady Flow and Vibration Analysis of the Horizontal-Axis Wind Turbine Blade under the Fluid-Structure Interaction - Rui Zhu; Da-duo Chen; Shi-wei Wu (Shock and Vibration)
A 1.5 MW horizontal-axis wind turbine blade and fluid field model are established to study the difference in the unsteady flow field and structural vibration of the wind turbine blade under one- and two-way fluid-structure interactions. The governing equations in ﬂuid field and the motion equations in structural were developed, and the corresponding equations were discretized with the Galerkin method. Based on ANSYS CFX fluid dynamics and mechanical structural dynamics calculation software, the effects of couplings on the aerodynamic and vibration characteristics of the blade are compared and analyzed in detail. Results show that pressure distributions at different sections of the blade are concentrated near the leading edge, and the leeward side of two-way coupling is slightly higher than that of one-way coupling. Deformation along the blade span shows a nonlinear change under the coupling effect. The degree of amplitude attenuation in two-way coupling is significantly greater than that in one-way coupling because of the existence of aerodynamic damping. However, the final amplitude is still higher than the one-way coupling. The Mises stress fluctuation in the windward and leeward sides is more obvious than one-way coupling, and the discrepancy must not be ignored.